2014
DOI: 10.1016/j.reprotox.2014.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Multigenerational exposure to dietary zearalenone (ZEA), an estrogenic mycotoxin, affects puberty and reproduction in female mice

Abstract: This study investigated potential cumulative effects of multiple pregnancy and multigenerational exposure to dietary ZEA (0, 0.8, 4, or 20 ppm) on female puberty and reproduction in C57BL/6J mice. Multiple pregnancies did not significantly affect litter size or offspring puberty. Significant effects were observed in 20 ppm ZEA-treated females: advanced puberty onset in F0, F1, and F2 generations; decreased implantation rate, pregnancy rate, and litter size, and increased pregnancy gap and gestation period in F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…Zearalenone (ZEA) is a toxic compound produced by several species of Fusarium and is found to cause mycotoxicosis in animals and humans [ 1 ]. It usually exists in contaminated livestock feed consumed by domestic animals, and is subsequently hazardous to the metabolism of organisms remarkably [ 2 , 3 ]. It is well known that both in females and males, the regulation of estrogen signaling is important in maintaining the normal functionality of reproductive systems [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zearalenone (ZEA) is a toxic compound produced by several species of Fusarium and is found to cause mycotoxicosis in animals and humans [ 1 ]. It usually exists in contaminated livestock feed consumed by domestic animals, and is subsequently hazardous to the metabolism of organisms remarkably [ 2 , 3 ]. It is well known that both in females and males, the regulation of estrogen signaling is important in maintaining the normal functionality of reproductive systems [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vaginal opening has been used as an early indicator of pubertal onset in rodents. It can be regulated by estrogen signaling because estrogenic endocrine disruptors could promote vaginal opening 19 20 21 22 23 , while anti-estrogens could delay vaginal opening 29 30 and estrogen signaling deficiency could lead to vaginal imperforation 31 in rodents. Vaginal imperforation has been observed in several mouse models, such as β-catenin C429S 32 , double deficiency of Bak and Bax 33 , over-expression of Bcl2 34 , triple deficiency of Bid, Bim, and Puma 35 , triple deficiency of Tyro3, Axl, and Mer 36 , deficiency of p63 37 , Movo1 38 , Pax8 39 , Grb10 40 , Glypican-3 41 , Map3k1 42 , EphA1 43 , Vangl2 44 , or Lrp2/Megalin 31 .…”
Section: Discussionmentioning
confidence: 99%
“…During the study of endocrine disruptors, we found that a few estrogenic endocrine disruptors could promote vaginal opening 19 20 21 22 23 , an early indicator of pubertal onset in mice 24 25 26 27 28 . It was our initial intention to use this Lhfpl2 mutant as a loss-of-function model for studying mechanisms of vaginal opening, which are not well understood.…”
mentioning
confidence: 99%
“…ZEA doses of 0 ppm (control), 0.8 ppm, 4 ppm, 10 ppm, and 40 ppm in the diets were used in our previous postweaning, premating, postmating, and/or multigenerational studies in mice [31,34]. These ZEA levels have been reported in the contaminated food [1][2][3][4], which must also have contamination of other mycotoxins, including other mycoestrogens.…”
Section: Dose Selection Treatment and Tissue Collectionmentioning
confidence: 99%